Multi-User Searchable Encryption Scheme for IoT Scenarios Based on Bloom Filter - YI Qiuzhi, TANG Hongbo, QIU Hang (Ji suan ji gong cheng, 2025)
Searchable encryption technology utilizes extracted keywords as indexes to search for specific documents within a document collection. However, existing searchable encryption schemes suffer from the issues of significantly increased resource consumption with an increased number of keywords and the inability to allow index collisions in multi-user scenarios. To address the limitations of the current schemes, a searchable encryption scheme for multi-user and multi-keyword scenarios in Internet of Things (IoT) environments is proposed. Leveraging the characteristics of Bloom filters, a memory-efficient vector is employed as an index for grouping document collections, thereby enhancing the efficiency of searchable encryption while permitting index collisions. A verification ciphertext generated from encrypted keywords is used to verify whether the trapdoor contains the keywords present in a document, thereby enabling users to locate matching documents within the shared-index document collection. Based on the discrete logarithm's hardness and the Diffie-Hellman problems, the proposed scheme requires fewer computational operations for ciphertext generation at each stage. Theoretical analysis and experimental results demonstrate that the scheme is both feasible and secure, with reduced communication overhead when compared with alternative approaches.